Dinamika hegemoni kuasa pada pendidikan Islam di Indonesia - Ahmad Baedowi (Indonesian Journal of Islamic Religious Education, 2023)
In history, power is something that is needed and able to influence human life. On the other hand, power sometimes uses various methods, both aggressive, agitative and subtle, in order to perpetuate the dominance and hegemony of its power. Likewise with the world of education. It cannot be separated from power. In fact, educational practices in Indonesia are still characterized by the hegemony of power, this is proven by the dichotomy and dualism of religious education and general education. This article tries to reveal the phenomenon of inequality and discrimination in education, especially religious education in Indonesia from an institutional perspective, using Antonio Gramsci's power hegemony approach. By using library research methods, this research shows that there are problems related to the dichotomy and dualism of religious education and general education, namely the tendency for the government to pay attention to general education and ignore religious education.